Plan de comunicación integral de la marca Veris como una estrategia de posicionamiento en el mercado de la atención médica ambulatoria privada en la ciudad de Quito, 2014 - Ron Donoso, Nadia Cleopatra (2014)
The communication plan is a useful tool to give a company an effective addressing that allows it to improve its internal and external communication, focused on strengthening the work environment and is necessary to achieve market positioning to obtain a higher profitability. This research focuses on the company Veris, which provides ambulatory health services with qualified personnel and cutting edge technology. Despite these strengths, the company has failed to maintain a right market positioning, with little recognition of the potential customers. Accordingly, it is essential to develop a plan consisting of several feasible strategies which enable the company to have a better and greater proximity to the market, allowing a steady growth. A methodology based on diagnostic was applied to have an updated SWOT which served as a foundation in the formulation of objectives, value propositions, strategies and tactics, developing an operational plan that will permit the company a proper implementation.